Seasonal Shifts in Diatom Species Dominance in the Tidal Mangrove Estuary of Bangladesh: Diatom species dominance in the tidal mangrove estuary (Journal of the Bangladesh Agricultural University, 2024)
Sustainable estuary management provides fishery resources, supports livelihoods and maintains estuarine food webs. However, these are highly dependent on hydrological factors and nutrients effects of the estuary itself. We studied seasonal phytoplankton quantity and composition of the Pasur River estuary in the Sundarbans mangrove forest, Bangladesh to understand the phytoplankton structure and identify potential indicators of environmental changes. Water and phytoplankton samples were collected at 11 different locations around the study region from January to December 2019 to assess spatial and temporal differences. Significant differences (p < 0.05) in the average salinity were observed between the dry and rainy seasons. Elevated phytoplankton (blue-green algae) concentrations were associated with decreased salinity while increased diatom abundance was linked to higher salinity. Phytoplankton succession from blue-green algae (wet season) to diatoms (dry season) occurred due to variations in physicochemical parameters and nutrient factors. Simultaneously, phytoplankton diversity and density were shown to change in response to habitat quality and seasonal variation. This study highlights the potential impacts of both human activities and natural factors on the population structure in these estuarine environments.J Bangladesh Agril Univ 22(2):231-240, 2024